Histologic chorioamnionitis in preterm infants: correlation with brain magnetic resonance imaging at term equivalent age - Claire Granger; Alicia J. Spittle; Jennifer Walsh; Jan Pyman; Peter J. Anderson; Deanne K. Thompson; Katherine J. Lee; Lee Coleman; Charuta Dagia; Lex W. Doyle; Jeanie Cheong (BMC, 2018)
Abstract Background To explore the associations between histologic chorioamnionitis with brain injury, maturation and size on magnetic resonance imaging (MRI) of preterm infants at term equivalent age. Methods Preterm infants (23-36 weeks' gestational age) were recruited into two longitudinal cohort studies. Presence or absence of chorioamnionitis was obtained from placental histology and clinical data were recorded. MRI at term-equivalent age was assessed for brain injury (intraventricular haemorrhage, cysts, signal abnormalities), maturation (degree of myelination, gyral maturation) and size of cerebral structures (metrics and brain segmentation). Histologic chorioamnionitis was assessed as a predictor of MRI variables using linear and logistic regression, with adjustment for confounding perinatal variables. Results Two hundred and twelve infants were included in this study, 47 (22%) of whom had histologic chorioamnionitis. Histologic chorioamnionitis was associated with higher odds of intraventricular haemorrhage (odds ratio [OR] (95% confidence interval [CI]) = 7.4 (2.4, 23.1)), less mature gyral maturation (OR (95% CI) = 2.0 (1.0, 3.8)) and larger brain volume (mean difference in cubic centimeter (95% CI) of 14.1 (1.9, 26.2)); but all relationships disappeared following adjustment for perinatal variables. Conclusion Histologic chorioamnionitis was not independently associated with IVH, less mature gyral maturation or brain volume at term-equivalent age in preterm infants.